The potency of ethanolic extract from corn silk as natural antibiotics for acne-related bacteria: A preliminary study (Bangladesh Journal of Medical Science, 2022)
Introduction: Corn silk or known as herb name stigma maydis is an important medicinal botanical in many traditional medicines worldwide, including jamu, an Indonesia traditional medicine. The exploration of corn silk to treat acne vulgaris is still lacking, therefore the current research was conducted to analyze the activity of ethanolic extract from corn silk (EECS) against 3 acne-related bacteria, Propionibacterium acnes, Staphylococcus epidermidis and Staphylococcus aureus.Materials and Methods: The antibacterial activity of EECS at concentration range of 10 to 100% v/v was evaluated using the disk diffusion method. As comparation, distilled water was used as a solvent control, while 1% clindamycin was used as a positive control.Results: Shinoda’s test showed that flavonoid was detected in the EECS. The higher concentration of EECS exhibited higher diameter of inhibition zone indicating higher antibacterial activity on P. acnes, while the antibacterial activity of S. epidermidis was not increased at similar concentrations of EECS. The antibacterial activity of EECS against S. aureus decreased at the higher EECS concentration (>70%).Conclusion: Taken together, EECS is a potential as a bioactive source to inhibit the growth of acne-related bacteria P. acne, S. epidermidis and S. aureus. Further investigation is needed to explore the corn silk or stigma maydis as a medicinal botanical in jamu targeted to treat acne vulgaris.Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 84-89